If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -12 = -5 + x Reorder the terms: -12 + -3x = -5 + x Solving -12 + -3x = -5 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -12 + -3x + -1x = -5 + x + -1x Combine like terms: -3x + -1x = -4x -12 + -4x = -5 + x + -1x Combine like terms: x + -1x = 0 -12 + -4x = -5 + 0 -12 + -4x = -5 Add '12' to each side of the equation. -12 + 12 + -4x = -5 + 12 Combine like terms: -12 + 12 = 0 0 + -4x = -5 + 12 -4x = -5 + 12 Combine like terms: -5 + 12 = 7 -4x = 7 Divide each side by '-4'. x = -1.75 Simplifying x = -1.75
| xa-7m=b(7k+x) | | 8x^2=-16x+31 | | ax-7m=b(7k+x) | | 7(4x-4)=28 | | 2x-2(4x-6)=-38 | | 5x+7=-128-10 | | -7(5c+9)-3(12+11c)= | | -19-3x=13x+9 | | 7(2-5x)+27=18x-3(8-4x) | | 4m-(m+6)=3m-4 | | 32-7x=2x+17 | | 5(7x-10)=x+3(2x+2) | | x^2+5k-6=0 | | 12x+5=6x+17 | | 5(c+9)=-3(2+c) | | 3x+9=-6x | | -10x-7(7-2x)=-71 | | x*5-89=x*2-11 | | 27=5u-3 | | 10+10(7+8m)=7(m+1) | | 4x^2+6=3x^2+18 | | 1000=10 | | 6x+8y=-16 | | 5x+9-(3x-13)=2(11+2x) | | 6r-25=-40+r | | x^2+10x-53=0 | | 5x+9=30 | | X-3(2x-7)+8=18 | | 19w+16=4(7+w) | | 8+10y-4=9y+36-7y | | (x)2+3x+2= | | 2x=5+x |